Water in Circular Economy and Resilience : The Case of Chennai, India - World Bank (World Bank, Washington, DC, 2021)
Chennai, a city on the southeastern coast of India and the state capital of Tamil Nadu, has one of the world’s fastest-growing economies. Chennai is the automotive hub for India and is also home to several other industries ranging from petrochemicals to hardware manufacturing, textiles, and apparel. Because of urbanization and economic growth, Chennai’s population has increased more than fifty percent over the past two decades. The city’s rapid growth has created several water challenges. This case study is part of a series prepared by the World Bank’s Water Global Practice to highlight existing experiences in the water sector. The purpose of the series is to showcase one or more of the elements that can contribute toward a Water in Circular Economy and Resilience (WICER) system. This case study focuses on the experience of Chennai in India.